The Meaning and Values Contained in the Traditional Music Performing Art of Gendang Guro-Guro Aron in Singa Village, Tiga Panah, Karo District - Gulo, Hubari; Ginting, Yoe Anto; Naiborhu, Torang (Formosa Journal of Science and Technology, 2023)
The traditional musical performance art Gendang Guro-Guro Aron Aron is an important part of the culture and identity of the people of Singa Village, Tiga Panah District, Karo Regency. This research aims to explore the meaning an d values contained in the performing arts. The research method used is a qualitative method with an interactive model. Data collection using participant observation, interviews, and literature study to holistically understand the Guro-Guro Aron Gendang. The research results show that the Guro-Guro Aron Gendang is not only entertainment but also contains religious, historical, and social meanings. This traditional music is a medium for conveying moral messages and local wisdom values that have been passed down from generation to generation. This research provides a deeper understanding of the rich culture and values that live in the traditional musical performance art Gendang Guro-Guro Aron.